Enhanced removal of coumarin by a novel O3/SPC system: Kinetic and mechanism. (March 2019) - Tan, Chaoqun; Xu, Qinglong; Zhang, Haochen; Liu, Zheming; Ren, Shuxin; Li, He
Abstract: A high-efficient, eco-friendly and applicable oxidant of percarbonate (SPC, Na2 CO3 ·1.5H2 O2 ) is applied as oxidant in ozonation (O3 ) process. In this work, coumarin (COU) decomposition by O3 and O3 /SPC was proposed in terms of diverse parameters, including ozone concentration, SPC dosage and pH, with regard to the pseudo-first-order kinetic model. About 96.5% of 25 mg L −1 COU was removed by 209.3 mg L −1 SPC and 2.08 mg L −1 O3 within 30 min, whereas 49.8% of COU was exhausted in O3 system alone. High ozone concentration and pH could enhance COU removal, and overdose SPC has an inhibition effect as CO3 2− could react with ·OH. Furtherly, the generation of hydroxyl radicals (OH) via a chain reaction in O3 was ascertained based on indirect alcohols quenching tests and direct electron spin resonance (ESR) spin-trapping tests, though high initial SPC concentration led to no trapping of OH by 5, 5-dimethyl-1-pyrroline-N-oxide (DMPO) in O3 /SPC. According to the concentration of dissolved ozone and prior study, a fast reaction kinetic model was estimated firstly for O3 /SPC system and well fitted with different condition. The hydroxylated intermediates of 7-hydroxylcoumarin and 6, 7-hydroxylcoumarin were recognized and the degradation pathways were proposed. The findings of the study can broaden the research direction of SPC and provide a new application information for SPC in environmental pollution control. Graphical abstract: Image 1 Highlights: O3 /SPC system is efficient for COU removal in 30 min. · OH was identified by EPR tests in O3 system. COU removal in O3 /SPC well fitted with pseudo first order kinetics pattern. A fast reaction kinetic model was estimated firstly for O3 /SPC system.